Back Cover: Phenotypic Screening to Identify Small‐Molecule Enhancers for Glucose Uptake: Target Identification and Rational Optimization of Their Efficacy (Angew. Chem. Int. Ed. 20/2014). Issue 20 (1st April 2014) - Koh, Minseob; Park, Jongmin; Koo, Ja Young; Lim, Donghyun; Cha, Mi Young; Jo, Ala; Choi, Jang Hyun; Park, Seung Bum
Abstract : The phenotype‐based discovery of novel therapeutic agents has suffered from the lengthy process of target deconvolution. In their Communication on page 5102 ff., S. B. Park et al. show that the convergent strategy of phenotype screening with early stage target identification can bridge the gap between phenotype‐based hit discovery and rational drug discovery to generate a new class of therapeutic agents. They were able to identify a new small‐molecule enhancer of cellular glucose uptake that targets PPARγ.